Sejarah Penulisan Aksara Arab Melayu dalam Tradisi Tulis dan Budaya Lokal - Nasywaa El Taqiyyah; Sri Mawaddah (Pustaka Digital Indonesia, 2025)
This study explores the historical significance of the Arabic-Malay script (Jawi) in shaping local literacy traditions and cultural identity in the Malay-speaking regions of Southeast Asia. The research aims to trace the development of Arabic-Malay writing and its relationship with Islamic scholarly transmission, customary law, and indigenous literature. Employing a descriptive qualitative method, the study analyzes historical documents, educational practices, and cultural artifacts related to the use of the script. Findings reveal that the Arabic-Malay script played a central role in disseminating Islamic knowledge, documenting local wisdom, and preserving oral traditions in written form. It served as a bridge between religious and secular spheres, fostering a literate society rooted in local values. The study concludes that the preservation and revitalization of Arabic-Malay writing are essential for sustaining cultural heritage and identity, particularly amid modern educational challenges and the decline of traditional literacy forms. Efforts such as integrating the script into school curricula, digital archiving, and community-based education are key to its survival.